TERAPAN BRAND â€œJOGJA ISTIMEWAâ€ TERHADAP PENGEMBANGAN PARIWISATA BERBASIS COMMUNITY BASED TOURISM (CBT) DI YOGYAKARTA - Irawati, Novi; Prakoso, Aditha Agung (Kepariwisataan: Jurnal Ilmiah, 2016)
The brand of â€œJogja Istimewaâ€ (Jogja is Special) is one of boosters of tourism development in Yogyakarta which increases each year. However, the role of this special status is not optimum yet when the society presenting Yogyakartaâ€™s local wisdom is not playing the roles. Realization of this special status is expected not only showing the image or marketing logo, but also it is required to form action from the society as the host. The implementation of local wisdom will bring positive impact for tourists. Keywords: Community Based Tourism, Tourism Marketing